TECHNICAL COMPETITION AS AN ELEMENT OF THE INCREASE OF BASIC- SCHOOL PUPILS' INTEREST IN THE TECHNICAL STUDY BRANCHES ABSTRACT - KVAPIL, Ludek (Trends in education, 2015)
The article state a relatively low interest of basic school pupils in a technical branches of study. It is focused on the possibilities to introduce pupils to the technical education in a form of competition to change the perception of technical education among the members of today's and future generation. It presents a "Technical competition" from a perspective of pupil's activation and their interest in technical education.
Keywords: Technical competition; creative product; technical education; pupil's skill; pupil's creativity; pupil's personality.